Involvement of women farmers in seed yam production in Abia state, Nigeria - Ironkwe, A.; Unamma, R.P.; Asiedu, Robert (2006)
A survey was conducted to assess the extent of women farmer's involvement in seed yam production in Abia State, Nigeria. Data were collected using intensive, schedule. The data collected were analysed using descriptive statistic. The results show that the mean age of the respondents was 47.7 years. Ninety seven percent 97% of the respondents were involved in seed yam production. While 93% were actively involved. However, lack of access to relevant farm inputs, the tediousness of the job, lack of access to agricultural information and assured marking outlets, were the most pressing problems encountered by the women farmers in seed yam production. It was recommended that the empowerment of women farmers through education, loans and organization into cooperatives would enhance women participation in seed yam production.